2018
DOI: 10.31235/osf.io/5zpm9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematically Monitoring Social Media: The Case of the German Federal Election 2017

Abstract: It is a considerable task to collect digital trace data at a large scale and at the same time adhere to established academic standards. In the context of political communication, important challenges are (1) defining the social media accounts and posts relevant to the campaign (content validity), (2) operationalizing the venues where relevant social media activity takes place (construct validity), (3) capturing all of the relevant social media activity (reliability), and (4) sharing as much data as possible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Another possibility would be a coordinated data collection effort-if the scope of public data access remains sufficient for such an endeavor. The "Social Media Monitoring" initiative by GESIS (Kaczmirek et al, 2014;Stier et al, 2018) is an interesting step in this direction. Yet the project is also confronted with many legal and ethical challenges beyond the technical implementation, ranging from data and privacy protection to copyright and the platforms' terms and conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possibility would be a coordinated data collection effort-if the scope of public data access remains sufficient for such an endeavor. The "Social Media Monitoring" initiative by GESIS (Kaczmirek et al, 2014;Stier et al, 2018) is an interesting step in this direction. Yet the project is also confronted with many legal and ethical challenges beyond the technical implementation, ranging from data and privacy protection to copyright and the platforms' terms and conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of both data sets revealed that the retrospectively collected data set missed a non-negligible amount of content compared to the rolling collection. The authors consequently decided to publish the latter data set (Stier et al, 2018).…”
Section: An Evaluation Of Retrospective Content Collection On Facebookmentioning
confidence: 99%
See 1 more Smart Citation
“…A rich corpus of work on prediction and analysis focuses on specific events with a large political scope. Since our work examines the political landscape in Germany, we particularly highlight a few papers concerned with the German Federal Elections in 2009 (Jungherr, Jürgens, & Schön, ; Tumasjan, Sprenger, Sandner, & Welpe, ), in 2013 (Jungherr, Schön, & Jürgens, ; Kaczmirek et al, ) and in 2017 (Stier et al, ). The working paper by Stier et al () like the present study, analyzes the German Federal Elections of 2017.…”
Section: Related Workmentioning
confidence: 99%
“…• Analysis of the political representativeness of Twitter users [3] • Real-time Twitter analysis [4][5][6] • Democratic elections [7][8][9][10][11][12][13] • The uses of Twitter by populists [14] • Misinformation dissemination and event detection in social networks [15][16][17] • Online public shaming [18] • and many more Furthermore, there exist plenty of public available datasets. E.g., a curated collection [19] is hosted on Zenodo [20] and covers several datasets of political campaigns [8,9], online misinformation networks [21], event detection in temporal networks [22], public shaming [23], Twitter-related word vectors [24], retweeting timeseries [25], and even continuously updated samples of a nations-wide Twitter usage [26].…”
Section: Introductionmentioning
confidence: 99%